1987
DOI: 10.1007/bf01974919
|View full text |Cite
|
Sign up to set email alerts
|

Relation between pharmacological response and receptor binding with histamine blocking drugs. Irreversible antagonism of three analogues of mifentidine on right atrium and cerebral cortex of the guinea-pig

Abstract: The effects of the H2-receptor antagonists cimetidine, ranitidine, mifentidine and three analogues of mifentidine, were studied on the spontaneously beating right atrium (H2-antagonism) and membranes of the cerebral cortex (displacement of 3H-tiotidine), both obtained from the male guinea-pig. The choice of these compounds was based on preliminary experiments in which some mifentidine analogues were shown to displace tiotidine from the H2-receptor in a deviant manner. In the present study we investigated the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A different number of spare receptors could also explain why APT and I-APT did not produce insurmountable antagonism in the right atrium (Hirschfeld et al, 1992); in this tissue, in fact, a receptor reserve of approximately 97% at maximal histamine responses has been calculated (Kramer et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A different number of spare receptors could also explain why APT and I-APT did not produce insurmountable antagonism in the right atrium (Hirschfeld et al, 1992); in this tissue, in fact, a receptor reserve of approximately 97% at maximal histamine responses has been calculated (Kramer et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The more pronounced rightward shift of the CRC to histamine observed in the papillary muscle in comparison with rat gastric fundus could be related to a larger receptor reserve for histamine H2 receptors in the heart, so that APT and I-APT, although reducing agonist-receptor occupancy will not produce a depression of the maximal response. A different number of spare receptors could also explain why APT and I-APT did not produce insurmountable antagonism in the right atrium (Hirschfeld et al, 1992); in this tissue, in fact, a receptor reserve of approximately 97% at maximal histamine responses has been calculated (Kramer et al, 1987).…”
Section: Insurmountable Antagonism By Apt and I-aptmentioning
confidence: 99%
“…The ratio E,E: E,Z is governed by the substituent R. The ratios E,E/E,Z were determined by NMR studies on the amidinimn cations (data not shown). Previously, we reported [1] receptor [3H]tiotidine displacement binding studies with some mifentidine analogues which instead of isopropyl contain higher alkyl-groups (as in mifentidine). The results indicated that these compounds bind irreversibly to sites different from tiotidine binding loci but allosterically influencing the interaction of tiotidine with the H2-receptor , causing pseudo-irreversible H2-antagonism by some kind of site-site interaction between the binding loci for the tested compounds and for histamine, leading to negative cooperativity.…”
Section: Introductionmentioning
confidence: 98%